Effects of the phloemic stress on the growth, development and quality of wax apple (Syzygium samarangense) cv. Jambu madu - Mohammad Moneruzzaman Khandaker,; Normaniza Osman,; Abm Sharif Hossain,; Amru Nasrulhaq Boyce, (Universiti Kebangsaan Malaysia, 2012)
A study was carried out to investigate the effects of different girdling techniques on the growth, development and quality of red wax apple fruits (Syzygium samarangense). Selected horticultural parameters were monitored at one week interval during the growth period from December 2008 to October 2010, using I, C, V shaped, 50%, and 100% girdling. Girdling was applied 2 weeks before flowering. The results showed that the C-shaped girdling technique produced the best results with regard to the fruit setting and chlorophyll content in comparison to the control and the other girdling techniques employed. Furthermore, C-shaped girdling enhanced faster fruit growth producing the best final fruit length and diameter. In addition to significantly increased yield, juice percentage, leaf dry matter, biomass and TSS content of fruits. It was also observed that 50% girdling decreased fruit dropping. V-shaped girdling also increased the number of bud and reduced bud dropping compared to control. I-shaped girdle fruits produced the highest amount of K+ content in fruit juice compared to other treatments. The color development of the fruit peel in 100% girdling was also the highest among the treatments. From this study, it can be concluded that C-shaped girdling applied two weeks before flowering produced better fruit growth, yield and quality of red wax apple fruits under field conditions.